THE IMPORTANCE OF ACTIVE GAMES AS A MEANS OF COMPREHENSIVE CHILD DEVELOPMENT - Saparbaev, Esen Tajibaevich (SCIENCE and SOCIETY, 2026)
In this article, the author, using various scientific materials on physical education, proves that the figurative explanation of outdoor games is one of the most important influencing factors, that this matter is especially important when talking about meaningful games and helps the participants in the game to correctly perform the tasks assigned to them. Information is provided that for students to thoroughly master the content of the game, it is necessary to use oral explanation in practice, that is, demonstrate various actions of the game.